The centipedes of Peloponnisos and first records of genus Eurygeophilus in the East Mediterranean (Myriapoda: Chilopoda) - Simaiakis, Stylianos Michail; Akkari, Nesrine; Zapparoli, Marzio (Zootaxa, 2016)
In this paper we summarize and critically revise the literature records of the centipedes of Peloponnisos in mainland Greece. Moreover, records on recently collected material in East Peloponnisos are included with a special focus on Mount Parnonas. Fifty centipede species are listed (1 Scutigeromorpha, 20 Lithobiomorpha, 6 Scolopendromorpha and 23 Geophilomorpha) belonging to 21 genera, 9 families and 4 orders. The species Eurygeophilus multistiliger (Verhoeff, 1899) is here reported for the first time not only from Greece but also from the East Mediterranean and the Balkan Peninsula. Additionally, the species Geophilus insculptus Attems, 1895, Stenotaenia rhodopensis (Kaczmarek, 1970) and Henia pulchella (Meinert, 1870) are newly recorded from Peloponnisos. Synonyms, general geographic distribution, patterns of distribution (chorotype), literature records, material examined from Mt. Parnonas, and ecological information (such as altitudinal ranges and habitat preferences) are given for each species. Remarks are additionally provided for some species and maps of species distribution in Peloponnisos are presented.